Robotic Writing Arm Based on Voice and Gesture Command for Physically Challenged - Godwin, J. Jijin; Shanmugaraj, G.; Harshithaa, M.; Sandhiya, K.; Suder, S.Arivu (International Journal of Psychosocial Rehabilitation, 2020)
Robots will be a powerful replacement of humans in the world future decades. Physically challenged people are facing difficulties to express their views to the world through alphabets. To overcome these hindrances many works have been proposed. In existence robots are trained to assist the physically challenged in writing by voice command or gesture command. The objective is to aid the physically challenged people to write virtually. Amputee and visually challenged are benefitted. Deep neural network algorithm is put forward. SIFT and classification model are the key ingredients of this algorithm. Three different inputs like voice command, camera-based input and MEMS hardware interface using ZigBee are given. In the proposed work, voice command is processed on an android application, image input is given through camera and gesture is given as input using MEMS. A robotic arm is designed, such that it writes alphabets on command. This approach aids the physically challenged people to translate the gestures and speech to written format.